GAMBARAN KENAKALAN REMAJA DI SEKOLAH DAN PERAN GURU BK DALAM PENANGANANNYA - Rosita, Tita; Annisa Rizki Ayu Leofianti; Maya Masyita Suherman; Rafi Naufal Hidayat (IKIP Siliwangi, 2025)
Juvenile delinquency is a behavior that causes social pathological symptoms in adolescents. The purpose of this study was to determine the aspects of delinquency committed by adolescents in the city of Cimahi and the urgency of the role of guidance and counseling teachers in handling it. The research method used is a quantitative approach with a survey method. The subjects in this study were adolescents who attended high school and vocational schools in the city of Cimahi. The sampling technique was random sampling so that 324 students were obtained consisting of 219 males and 105 females. Based on the results of the study, juvenile delinquency in the aspect of delinquency in school is the highest category compared to aspects of interpersonal aggression, theft & vandalism, and substance abuse. Delinquency behavior in school in this study included truancy, being late to school, cheating, and arguing with teachers. The average age when they first committed delinquency was 15 years old and students whose parents were divorced had a high average value for juvenile delinquency. The most common punishments given by teachers at school to their students were pinching, humiliating, and running around the school field. Based on this, guidance and counseling teachers need to have four strategies, namely (1) building communication with students without judging, (2) building trust in students, (3) not giving negative labels or negative stigma to students, and (4) enforcing restorative justice policies.